2018
DOI: 10.1177/1759720x18812449
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pain and symptoms in pregnancy: a descriptive study

Abstract: Background:Pregnancy-induced hormonal and physiologic changes increase the risk of musculoskeletal problems in pregnancy. The purpose of this report is to provide a comprehensive look at the musculoskeletal pain and symptoms experienced during pregnancy.Methods:A total of 184 women (mean age 30.9 ± 5.0 years) who gave birth in the obstetrics clinic of a tertiary hospital were included in the study. The participants who had given birth at 37–42 weeks of pregnancy (term pregnancy) and aged over 18 years were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 19 publications
(31 reference statements)
2
49
1
4
Order By: Relevance
“…In our study, a large proportion of pregnant women (71.7%) experienced LCs during this current pregnancy. This proportion was slightly lower than the reported study in Turkey (75%) (Kesikburun et al, 2018). Other international studies stated the following prevalences of LCs, i.e.…”
Section: Figure 1: Study Low At the Health Cliniccontrasting
confidence: 69%
See 1 more Smart Citation
“…In our study, a large proportion of pregnant women (71.7%) experienced LCs during this current pregnancy. This proportion was slightly lower than the reported study in Turkey (75%) (Kesikburun et al, 2018). Other international studies stated the following prevalences of LCs, i.e.…”
Section: Figure 1: Study Low At the Health Cliniccontrasting
confidence: 69%
“…The prevalence of LCs in pregnancy ranges from 18.2% to 75%. The lowest prevalence was in Australia while the highest prevalence was in Turkey (Hall et al, 2016;Kesikburun et al, 2018). Pregnant mothers in their second or third trimesters are more affected (Ramachandra et al, 2015;Hensley, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…[1] A plethora of prospective and retrospective studies exist regarding the epidemiology of pregnancy-related back pain, and the prevalence ranges from 25% to 90%. [234567891011] Pregnancy-related LBP usually begins between the 20 th and the 28 th weeks of gestation, and the exact duration varies. [12]…”
Section: Introductionmentioning
confidence: 99%
“…In our study, although there were some significant correlations between duration of pain and pre-partum maternal weight and between change in maternal BMI and gestational age at the onset of pain in the painful group, we found no difference between maternal height/weight, prepregnancy/pre-partum BMI, and change in maternal BMI and the development of low back pain between the painful and painless groups. On the other hand, although a previous study suggested that the male sex of the fetus may be a predictor factor for low back pain during pregnancy, numerous other studies implicated that there is no such association (3,17,18).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, low back pain often begins between the 20th and 28th weeks of gestation and the reported incidence of low back pain in pregnant women ranges between 14-90% (6,7). However, the mean incidence has been shown to be 25% in pregnant women, as compared to 6.3% in non-pregnant women of the same ages (1)(2)(3)(4). Most of the treatment methods used for low back pain cannot be used in pregnant women.…”
Section: Introductionmentioning
confidence: 99%